Quality indicators and patients' characteristics in relation to early outcome of Kasr-al-ainy stroke unit - Maha Atef Zaki; Ahmed Mohamed Abdelalim; Husam Salah Mourad; Abdallah Adel Saad; Amr Mohamed Fouad (The Egyptian Journal of Neurology, Psychiatry and Neurosurgery, 2023)
Abstract Background A wide variety of factors have been reported to influence stroke prognosis. Quality indicators serve as standards of care. The aim of this study is to assess the clinical and demographic characteristics of patients with stroke and to measure quality indicators in relation to stroke early outcome. We analyzed a prospective hospital-based data. All patients with acute stroke admitted to Kasr-al-ainy stroke unit over a 1-year period were included. Clinical variables and quality indicators were studied in relation to early outcome which was measured by both disability at discharge assessed by modified Rankin score (mRS) and in-hospital death. Results We studied 242 patients with acute stroke, 145 patients (59.9%) had poor outcome at discharge [mRS 3–6]. There were 36 (14.9%) in-hospital deaths. High mRS and National institute of health stroke scale (NIHSS) at stroke onset, low Gugging swallowing scale (GUSS) score and hypertension (HTN) were independent predictors for more disability on discharge. Chest infection, bed sores, high mRS at stroke onset and hemorrhagic transformation were independent predictors for in-hospital mortality. Receiving recombinant tissue plasminogen activator (rtPA) showed significant association with good outcome. Mean door to needle time (DNT) was 50.6 min. Low GUSS score was associated with increased risk of chest infection. Conclusions Stroke severity, potentially modifiable risk factors and complications are associated with an increased risk of poor early outcome. Dysphagia screening using GUSS scale can predict patients with higher risk of aspiration pneumonia after stroke. DNT needs to be improved.